MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI MENGGUNAKAN METODE DISCOVERY LEARNING PADA SISWA KELAS X SMA BUDI SATRIA BANDAR SELAMAT TAHUN PEMBELAJARAN 2021-2022 - Riski Rahmadini; Fata Ibnu Hajar (Bajang Institute, 2024)
This research aims to evaluate the effectiveness of using learning using the Discovery Learning method for students in class X-MIPA 2 Budi Satria Bandar Selamat in Indonesian language subjects. Apart from that, this research also aims to analyze student learning outcomes before and after implementing learning using the Discovery Learning method. The variables in this research consist of learning using the Discovery Learning method as the independent variable and student learning outcomes as the dependent variable. The data analysis methods used include descriptive data analysis techniques and inferential statistical analysis. The research results show that before implementing learning using the Discovery Learning method, the average student learning outcome was 70. After implementing this model, the average student learning outcome increased to 78.46. This indicates an increase in the average student score of 8.46. These results provide evidence that the use of learning using the Discovery Learning method has a positive impact on students' ability to write expository texts